Integral Cost-Benefit Analysis of Maglev Rail Projects Under Market Imperfections - J. Paul Elhorst; Jan Oosterhaven (Journal of Transport and Land Use)
This article evaluates a new mode of high speed ground transportation, the magnetic levitation rail system (Maglev). The outcomes of this evaluation provide policy information on the interregional redistribution of employment and population and the national welfare improvement of two Dutch urban-conglomeration and two Dutch core-periphery projects. This article also compares the results of an integral cost- benefit analysis with those of a conventional cost-benefit analysis and concludes that the additional economic benefits due to market imperfections vary from –1% to +38% of the direct transport benefits, depending on the type of regions connected and the general condition of the economy.